Calicivirus Non-structural Proteins: Potential Functions in Replication and Host Cell Manipulation - Smertina, Elena; Hall, Robyn N.; Urakova, Nadya; Strive, Tanja; Frese, Michael (Frontiers in Microbiology, 2021)
The Caliciviridae are a family of viruses with a single-stranded, non-segmented RNA genome of positive polarity. The ongoing discovery of caliciviruses has increased the number of genera in this family to 11 (Norovirus, Nebovirus, Sapovirus, Lagovirus, Vesivirus, Nacovirus, Bavovirus, Recovirus, Salovirus, Minovirus, and Valovirus). Caliciviruses infect a wide range of hosts that include fish, amphibians, reptiles, birds, and marine and land mammals. All caliciviruses have a genome that encodes a major and a minor capsid protein, a genome-linked viral protein, and several non-structural proteins. Of these non-structural proteins, only the helicase, protease, and RNA-dependent RNA polymerase share clear sequence and structural similarities with proteins from other virus families. In addition, all caliciviruses express two or three non-structural proteins for which functions have not been clearly defined. The sequence diversity of these non-structural proteins and a multitude of processing strategies suggest that at least some have evolved independently, possibly to counteract innate and adaptive immune responses in a host-specific manner. Studying these proteins is often difficult as many caliciviruses cannot be grown in cell culture. Nevertheless, the study of recombinant proteins has revealed many of their properties, such as intracellular localization, capacity to oligomerize, and ability to interact with viral and/or cellular proteins; the release of non-structural proteins from transfected cells has also been investigated. Here we will summarize these findings and discuss recent in silico studies that identified previously overlooked putative functional domains and structural features, including transmembrane domains that suggest the presence of viroporins.